Collaboration and teacher knowledge in a teacher learning community: A case of mathematics teachers in KwaZulu-Natal province - Zulu, F-Q.B.; Bertram, C. (South African Journal of Higher Education, 2019)
The literature on professional development of teachers has shifted to focusing on collaboration and learning communities as a productive way for teachers to learn. This qualitative case study examines the nature of collaborative activities and the kinds of teacher knowledge learnt in a community of high school mathematics teachers. Data was collected through observations of professional development workshops, questionnaires, interviews with teachers and document analysis. The findings established that collegial collaboration and the focus on specialised content knowledge in this learning community enabled teachers to approach their teaching more effectively. In this paper we claim that that the learning community is a productive learning space because it was supported by the Department of Education and a Non-Governmental Organisation, and because it focused on specialised content knowledge. The collaborative focus enabled teachers to share knowledge and ideas resulting in teachers taking charge of their own learning.